Pemanfaatan Web Based Learning Terhadap Hasil Belajar Sejarah Bagi Siswa di SMA Negeri 2 Palu - Hasan Hasan; Misnah Misnah; Mutawakkil Mutawakkil; Ketut Ardana (Jurnal Kreatif Online, 2023)
The purpose of this study was to determine the effect of using Web Based Learning using the Google Sites Web on history learning outcomes for students in class XI IPS 1 SMA Negeri 2 Palu. This study uses a quasi-experimental design. The design of this study used a nonequivalent control group design involving an experimental class and a control class. The results of the research in the experimental class obtained the average data on pre-test learning outcomes of 9.47, post-test of 15.60 and gain of 6.13. While the results of the study in the control class obtained the average data on pretest learning outcomes of 6.66, posttest of 9.83 and gain of 3.17. Based on the results of the hypothesis test, it can be interpreted that there is a significant difference between the learning outcomes of history for students who apply the use of Web Based Learning and those who do not apply the use of Web Based Learning. This means that there is an effect of using Web-Based Learning on history learning outcomes for students at SMA Negeri 2 Palu.